1987
DOI: 10.1002/zaac.19875470404
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis der kristallinen Phasen in den Systemen MOAl2O3H2O (MI = K, Na)

Abstract: Im System K2OAl2O3H2O existieren die Verbindungen K2O · Al2O3 · 3 H2O, K2O · Al2O3 · 2 H2O und K2O · Al2O3 · 1 H2O. Die Ergebnisse von 27Al‐NMR‐, 1H‐NMR‐ und IR‐spektroskopischen sowie thermoanalytischen Untersuchungen bestätigen für das 3‐Hydrat das Vorliegen dimerer Anionen mit tetraedrisch koordiniertem Al und zeigen, daß in den beiden anderen Hydraten höhermolekulare, ebenfalls aus AlO4‐Gruppen aufgebaute Anionen auftreten. Im System Na2OAl2O3H2O werden eine Verbindung der Zusammensetzung Na2O · Al2O3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Such observations indicate that the Al 3+ coordination change occurs either on the NSA crystal surface or during a solid-state amorphous-to-crystalline transition but not in solution. Given that the isolation of Na 2 Al 2 O­(OH) 6 has eluded many others exploring the Na 2 O/Al 2 O 3 /H 2 O phase space, it is reasonable to infer from the instability of Na 2 Al 2 O­(OH) 6 that it may exist as a reactive intermediate during solid-state crystallization, linking the soluble tetrahedral aluminates under highly alkaline conditions to the monomeric octahedra in NSA. Further isolation of crystallization pathways, including the prospect of solid-state transformation, is underway to better understand Al 3+ coordination change mechanisms in caustic environments relevant to myriad process applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such observations indicate that the Al 3+ coordination change occurs either on the NSA crystal surface or during a solid-state amorphous-to-crystalline transition but not in solution. Given that the isolation of Na 2 Al 2 O­(OH) 6 has eluded many others exploring the Na 2 O/Al 2 O 3 /H 2 O phase space, it is reasonable to infer from the instability of Na 2 Al 2 O­(OH) 6 that it may exist as a reactive intermediate during solid-state crystallization, linking the soluble tetrahedral aluminates under highly alkaline conditions to the monomeric octahedra in NSA. Further isolation of crystallization pathways, including the prospect of solid-state transformation, is underway to better understand Al 3+ coordination change mechanisms in caustic environments relevant to myriad process applications.…”
Section: Discussionmentioning
confidence: 99%
“…One potentially important species is the μ-oxo aluminate dimer (Al 2 O­(OH) 6 2– ), which can form by oxolation in solution and, in concentrated potassium and rubidium hydroxide, leads directly to crystallization of M 2 Al 2 O­(OH) 6 salts (M = K + or Rb + ), principally comprised of this dimer motif. ,, However, crucially, in the sodium system, no comparable sodium aluminate dimer crystal structure has been found despite thorough exploration of the Na 2 O/Al 2 O 3 /H 2 O phase diagram. Analysis of the formation, reactivity, and dynamics of Al 2 O­(OH) 6 2– in solution is challenging because of rapid exchange of Al 3+ ion speciation through hydrolysis and condensation during nuclear magnetic resonance (NMR) spectroscopy, ,,,, degenerate Raman-active vibrational modes, nonmonotonic trends in pre-edge features in X-ray absorption spectroscopy, and multimodal relaxation processes in both dielectric spectroscopy and quasielastic neutron scattering . Among such techniques, the most diagnostic is Raman spectroscopy, which clearly shows that vibrational modes of sodium aluminate solutions contain a component similar to that of K 2 Al 2 O­(OH) 6 . ,, …”
Section: Introductionmentioning
confidence: 99%
“…At low total [NaOH], gibbsite, its structural polymorph bayerite, and boehmite are the solubility-controlling phases, and these minerals have octahedrally coordinated Al in a hydroxy- or oxy-bridged network. However, when total Na + /Al­(OH) 4 – ratios are greater than 1 and total [NaOH] is above ∼10 m (molality), gibbsite (or bayerite or boehmite) gives way to solubility-controlling phases of (1) monosodium aluminate hydrate (Na 2 [Al 2 O 3 (OH) 2 ]·1.5H 2 O) composed of chains of tetrahedral aluminates each coordinated to three bridging oxygens and one terminal hydroxy group and/or (2) nonasodium bis­(hexahydroxy aluminate) trihydroxide hexahydrate (Na 9 [Al­(OH) 6 ] 2 (OH) 3 ·6H 2 O), in which aluminum speciates as monomeric aluminate octahedra coordinated to six hydroxides. It is noteworthy that none of the crystalline solids in the sodium case have any significant topological resemblance to the monomeric Al­(OH) 4 – and μ-oxo-bridged dimeric Al 2 O­(OH) 6 2– speciation in solution …”
Section: Introductionmentioning
confidence: 99%
“…Fricke et al determined the solid phase of potassium aluminate hydrate as KAlO 2 ·2H 2 O by using Schreinemaker’s method. Gessner et al reported that potassium aluminate crystals, K 2 O·Al 2 O 3 ·3H 2 O, K 2 O·Al 2 O 3 ·2H 2 O, K 2 O·Al 2 O 3 ·H 2 O, and K 2 O·Al 2 O 3 could be respectively obtained at high temperatures of 403.15, 423.15, 643.15, and 773.15 K, and also investigated the crystal lattice parameters. Only Du measured the phase equilibria for the ternary system K 2 O–Al 2 O 3 –H 2 O at 313.15 K by the isothermal method, and showed that the equilibrium solid-phase K 2 O·Al 2 O 3 ·3H 2 O was found besides KOH·H 2 O in the concentrated alkali region of the phase diagram.…”
Section: Introductionmentioning
confidence: 99%
“…Fricke et al3 determined the solid phase of potassium aluminate hydrate as KAlO 2 •2H 2 O by using Schreinemaker's method. Gessner et al17 reported that potassium aluminate crystals, K 2…”
mentioning
confidence: 99%